2018
DOI: 10.1002/er.4115
|View full text |Cite
|
Sign up to set email alerts
|

A novel multilayer fin structure for heat transfer enhancement in hydride-based hydrogen storage reactor

Abstract: Summary Metal hydrides are promising means for compact hydrogen storage. However, the poor heat transfer in the tank packed with metal hydride powders often hinders the system from charging or discharging hydrogen effectively. In this investigation, a tube‐fin heat exchanger is supposed to be inserted to the tank, and an optimization problem accounting for both heat transfer enhancement and cost is formulated. We solve the problem with approximate analytical methods, and the influences of fin geometry are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Subsequently, Kou et al presented a thin double annulus MHB, suggesting that the presented reactor could effectively enhance the hydrogen storage performance. Zhang et al proposed a distinctive reactor structure for improving the heat exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Kou et al presented a thin double annulus MHB, suggesting that the presented reactor could effectively enhance the hydrogen storage performance. Zhang et al proposed a distinctive reactor structure for improving the heat exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Garrison et al optimized the internal heat exchangers for enhancing the hydrogen storage tanks utilizing metal hydrides. Dhaou et al and Zhang et al used the fin and finned spiral heat exchanger to enhance the H 2 storage, respectively. Besides, the adsorption tank is usually equipped with a phase-change material (PCM) jacket because the PCM has a high energy storage capacity and a negligible temperature variation during the operation process. , The PCM can adsorb the accumulated heat released by gas adsorption in MOFs and then release heat during gas desorption in MOF materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that iron carbide was detected during milling, which act as a catalyst and increased hydrogen storage capacity. In another study, 10 a new multi‐layer fin geometry design is proposed and analyzed to study the heat transfer behavior of MH reactor (filled with LaNi 5 ) during hydrogenation and dehydrogenation processes. Tubular fins are introduced radially in the reaction chamber with a cooling water circulation arrangement at the center of the cylinder (reactor).…”
Section: Introductionmentioning
confidence: 99%